Comparison of clinical features and outcomes of patients with leiomyosarcoma of bone and soft tissue: a population-based cohort study. (18th November 2021) - Kobayashi, Hiroshi; Zhang, Liuzhe; Hirai, Toshihide; Tsuda, Yusuke; Ikegami, Masachika; Tanaka, Sakae
Abstract: Background: Leiomyosarcoma commonly occurs in soft tissue but rarely in the bone. Whether leiomyosarcoma of bone and soft tissue have similar clinical characteristics and outcomes remains unknown. Methods: This retrospective analysis was based on data from the Bone and Soft Tissue Tumor Registry in Japan. Patients with leiomyosarcoma of bone and soft tissue were enrolled. Overall survival and distant metastasis-free survival were estimated using the Kaplan–Meier method, and the Cox regression model was used to identify the prognostic factors. Results: A total of 888 patients (60 leiomyosarcoma of bone and 828 leiomyosarcoma of soft tissue) were included in the study. Clinical characteristics were similar between the two groups, except for younger age in leiomyosarcoma of bone than in leiomyosarcoma of soft tissue (median 56 years vs. 66 years, P < 0.0001). To evaluate the prognostic factors and efficacy of adjuvant chemotherapy, data of localized and locally curative cases were extracted (total 572: 33 leiomyosarcoma of bone and 539 leiomyosarcoma of soft tissue). The 5-year overall survival rates of leiomyosarcoma of bone and soft tissue patients were similar (63.8% vs. 75.2%, P = 0.43); the 5-year distant metastasis-free survival tended to be worse in leiomyosarcoma of bone than in leiomyosarcoma of soft tissue (37.4% vs. 57.9%, P = 0.28). Larger tumor size (≥5 cm) and older age (≥65 years) correlated with poor overall survival in leiomyosarcoma of soft tissue patients. Adjuvant chemotherapy tended to prolong the overall survival of both leiomyosarcoma of bone ( P = 0.11) and leiomyosarcoma of soft tissue patients with tumor size >10 cm ( P = 0.06). Conclusions: The clinical characteristics and outcomes of leiomyosarcoma of bone and soft tissue patients were similar. In localized cases, adjuvant chemotherapy may improve the survival of leiomyosarcoma of bone and soft tissue patients with large-size tumor. Abstract : Patients with leiomyosarcoma of the bone and soft tissue had similar clinical characteristics and outcomes. Adjuvant chemotherapy may improve the survival of some patients with leiomyosarcoma.